2007
DOI: 10.1111/j.1398-9995.2007.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐assessment of disease‐specific quality of life questionnaires for rhinitis and rhinosinusitis: a systematic review

Abstract: The aim of this systematic review was to give a quality‐assessed review of the existing disease‐specific health related quality of life (QOL) questionnaires concerning rhinitis and rhinosinusitis for adults. The quality is assessed by defining the characteristics of a QOL questionnaire with assessment criteria. The results of the construction, description, feasibility, and the psychometric performance of the instruments are provided. We finally provide a clinician’s guide to choose a questionnaire based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 63 publications
3
72
0
15
Order By: Relevance
“…Therefore, specific questionnaires are preferrable 5 . Two recent reviews have identified numerous outcome measure questionnaires used to assess patients with rhinitis and rhinosinusitis, both acute and chronic, evaluating them as to reliability, validity, responsiveness and ease of use 6,7 . As more outcome measure questionnaires are developed, there is the need to have an agreement among the many authors in the world, so as to standardize the assessment of rhinosinusitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, specific questionnaires are preferrable 5 . Two recent reviews have identified numerous outcome measure questionnaires used to assess patients with rhinitis and rhinosinusitis, both acute and chronic, evaluating them as to reliability, validity, responsiveness and ease of use 6,7 . As more outcome measure questionnaires are developed, there is the need to have an agreement among the many authors in the world, so as to standardize the assessment of rhinosinusitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…AR does not merely cause nasal discomfort due to persistent nasal symptoms, but also leads to losses in concentration and headaches, which can affect sleep, social interaction, school work, and even workplace productivity, leading to socioeconomic losses [29]. Studies have shown improvement in QOL using various parameters including RQLQ, which was used in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Kalite puanı en yüksek olan anketlerden rinit için RQLQ ve RQLQ(S) ve rinosinüzit için RSOM-31 ve Rhino-QoL anketlerinin ayırt edici geçerlilik ve duyarlılık kriterlerine de uyarak en iyi anketler olarak klinisyene önerilmiştir. 6 Baumann KRS'te subjektif sonuçları değerlen-diren derlemesinde, geçerlilik çalışmaları da yapı-lan ölçeklerden, sadece dördünün KRS'in tüm ana semptomlarını değerlendirdiğini bildirmiştir. Bunlar Fairley'nin nazal semptom anketi, SNQA-11, SN-5 ve SNOT-20'nin Alman adaptasyondur.…”
Section: öZgül Yaşam Kali̇tesi̇ öLçekleri̇ne Genel Bakişunclassified
“…5 Bu ciddi mali portrenin yanında rinit ve rinosinüzitler yaşam kalitesinde de anlamlı değişikliğe sebep olurlar. 6 Yaşam kalitesi ölçekleri bir hastalığın ve tedavisinin etkilerini değerlendirmede kapsamlı bilgi sağlar. Tıp biliminde klasik olarak hastalık seyri, laboratuvar, görüntüleme yöntemleri ve klinik testlerle değerlendirilir.…”
unclassified